Analisis Pengaruh Atmosfer Cafe Terhadap Keputusan Pembelian Produk Coffe pada Masyarakat Karawang - Celvin Surya Dharma; Hawignyo Hawignyo (Universitas Batanghari, 2022)
The purpose of this study was to analyze the effect of the cafe atmosphere on the interest in buying Kaula coffee products in the Karawang community. There are two key respondents who became informants in this study. This study uses a qualitative approach, and data collection techniques through interviews. From this study, it was found that the cafe atmosphere had an effect on people's buying interest, a comfortable outdoor atmosphere and live music could increase people's purchasing power for Kaula coffee products. In addition, it was found that the rainy season had an impact on the decrease in the number of visitors because Kaula Coffee used the Outdor theme.